Innocence Mortality Tax: The Impact of Wrongful Conviction on Lifespan - Catlin, Mary; Redlich, Allison D. (The Wrongful Conviction Law Review, 2023)
The wrongful conviction of innocent individuals is a growing problem for those unjustly convicted and the integrity of our legal system, with exonerees often struggling post-exoneration. Yet, too little is known about the long-term impact of wrongful convictions on those unjustly convicted. Thus, we investigated the effect of wrongful conviction on mortality and lifespan—that is, we tested for the possibility of an “innocence mortality tax.” We found that more exonerees have passed than expected when compared to U.S. death rates, and that exonerees died 13.24 years earlier than expected, given their age, gender, race/ethnicity, and incarceration length. Finally, those exonerees whose cases involved a false confession or mistaken eyewitness identification died significantly sooner than their counterparts. Our results highlight the need for researchers, practitioners, and policymakers to continue to find ways to mitigate the harm done to innocent individuals unjustly convicted.